Association of microalbuminuria and serum uric acid levels in patients with Type 2 diabetes mellitus - Gautam, Bijaya; Poudel, Satish; Pokhrel, Shanti (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Microalbuminuria is associated with increased risk of progressive kidney disease, leading towards end-stage renal disease and cardiovascular morbidity and mortality in diabetic patients. Elevated serum uric acid is a feature of hyperinsulinemia/insulin resistance. Insulin normally promotes renal tubular sodium and uric acid reabsorption. In hyperinsulinemia (which occurs in insulin resistance), increased insulin levels lead to decreased excretion of uric acid by the kidneys. So, Serum uric acid increases due to impaired clearance. The interrelationship between uric acid levels and the onset or progression of microalbuminuria remains incompletely understood. The measurement of uric acid in laboratories is fast, simple, and affordable. So, this study was performed to assess the significance of microalbuminuria and uric acid in the early detection of renal and cardiovascular involvement in type 2 diabetes mellitus and early prevention of complications. Methods: A hospital-based cross-sectional study was conducted on 106 patients who had type 2 diabetes mellitus. Random spot urine and venous blood samples were collected, labelled, and stored. The urine microalbumin and serum level of uric were measured by nephelometry method using Mispa i3 and the spectrophotometry method using semi-automated analyzer Erba CHEM7. Results: There was a significant association of microalbuminuria with duration of diagnosis (p-value=0.001) while no association with age and gender. Similarly, there was a significant association of serum uric acid with duration of diagnosis (p-value=0.009) while no association with age and gender. There was a significant association of urinary microalbumin and serum uric acid in type 2 diabetes mellitus (p-value=0.001). Conclusions: The present study showed a significant association of microalbuminuria with the duration of diabetes. A significant association was observed between the duration of diabetes and development of micro and subsequently macroalbuminuria.